Serum Vitamin D in Patients with Chronic Periodontitis and Healthy Periodontium - pradhan, Shaili; Agrawal, Shweta (Journal of Nepal Health Research Council, 2021)
Background: Periodontitis is inflammatory disorder resulting in progressive destruction of the periodontal ligament and alveolar bone with pocket formation, recession, or both. Vitamin D has a benefit in bone metabolism and anti-inflammatory activity involving T-cell homeostasis. The objective of this study was to compare the vitamin D level in patient with chronic periodontitis and healthy periodontium and evaluate its correlation.Methods: A comparative cross-sectional study was done in 80 patients (40 with healthy periodontium and 40 with chronic periodontitis) visiting to Department of Dental Surgery (Periodontology and Oral Implantology Section) of Bir Hospital. Parameters measured were plaque index, gingival index, clinical attachment level and pocket depth for the evaluation of healthy periodontium and chronic periodontitis. Results: The result showed 16.58±6.65ng/mL and 19.06±11.52ng/mL level of vitamin D in female and male respectively (p-value 0.230) and 16.85±13.30 ng/mL and 19.78±5.87 ng/mL level of vitamin D in healthy and chronic periodontitis groups respectively (p-value 0.209).Conclusions: There are no differences in the level of serum vitamin D between healthy and chronic periodontitis groups. No association was seen between vitamin D level and chronic periodontitis.Keywords: Bone metabolism; chronic periodontitis; clinical attachment level; healthy periodontium; vitamin D; periodontal pocket